2017
DOI: 10.1590/0001-3765201720160496
|View full text |Cite
|
Sign up to set email alerts
|

First Assessment of Carbon Stock in the Belowground Biomass of Brazilian Mangroves

Abstract: Studies on belowground roots biomass have increasingly reported the importance of the contribution of this compartment in carbon stock maintenance in mangrove forests. To date, there are no estimates of this contribution in Brazilian mangrove forests, although the country has the second largest area of mangroves worldwide. For this study, trenches dug in fringing forests in Guaratiba State Biological Reserve (Rio de Janeiro, Brazil) were used to evaluate the contribution of the different classes of roots and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…Furthermore, a higher AGB carbon value than average was also determined in this study (180.3 Mg C ha −1 ), when compared with the mean AGB carbon values of 40.2 and 125 Mg C ha −1 for Australian [92] and New Zealand [93] mangroves, respectively. Contrastingly, and despite a higher than average value for AGB carbon, the BGB carbon values calculated for the three locations averaged at 84.6 Mg C ha −1 , much lower than the largest reported value worldwide (263 Mg C ha −1 ), and still significantly lower than an average obtained for a study in Brazil (104.4 Mg C ha −1 ) by Santos et al [94]. These discrepancies could be explained by the hydrogeomorphic setting directing the mangrove's blue carbon stock dynamics, in parallel to long-term transformations of landuse having a significant impact on carbon gains and losses [24].…”
Section: Discussioncontrasting
confidence: 82%
“…Furthermore, a higher AGB carbon value than average was also determined in this study (180.3 Mg C ha −1 ), when compared with the mean AGB carbon values of 40.2 and 125 Mg C ha −1 for Australian [92] and New Zealand [93] mangroves, respectively. Contrastingly, and despite a higher than average value for AGB carbon, the BGB carbon values calculated for the three locations averaged at 84.6 Mg C ha −1 , much lower than the largest reported value worldwide (263 Mg C ha −1 ), and still significantly lower than an average obtained for a study in Brazil (104.4 Mg C ha −1 ) by Santos et al [94]. These discrepancies could be explained by the hydrogeomorphic setting directing the mangrove's blue carbon stock dynamics, in parallel to long-term transformations of landuse having a significant impact on carbon gains and losses [24].…”
Section: Discussioncontrasting
confidence: 82%
“…Estimated mean±standard error of the below-ground biomass (BGB), above-ground biomass (AGB), total biomass (Mg ha -1 ), and the BGB:AGB ratio, and the respective values of carbon storage recorded for each height class. The BGB estimates available for mangrove forests around the world have been obtained using a range of both direct and indirect approaches, such as the trench method [26], extraction (pull up) [72], and the analysis of soil cores [79], resulting in highly diverse biomass estimates [31]. The root sampling method adopted in the present study has been applied successfully in previous studies of mangroves [38,71] and other types of tropical forest around the world [84].…”
Section: Plos Onementioning
confidence: 99%
“…Studies of biomass production and carbon storage have focused on different types of mangrove forest around the world, including fringe [19], basin [20], riverine [21], and scrub [19] forest types, which have generated an ample range of estimates (~8-460 Mg ha -1 ), reflecting the diversity of environmental conditions. Most estimates of the production of biomass and carbon storage by mangrove ecosystems have focused on well-developed forests [22][23][24][25][26], while the effects of stressful conditions have been largely overlooked. As few studies have focused specifically on these stressed forests of short stature [19,27,28], it is important to develop allometric equations that provide reliable estimates of their biomass, not only because this vegetation is characterized by considerable morphological variation [29] and is widely distributed in tropical and subtropical regions [30], but also because these equations will help to minimize the uncertainties intrinsic to the estimates of productivity available for the world's mangrove ecosystems as a whole [31].…”
Section: Introductionmentioning
confidence: 99%
“…While mangroves are widespread in Brazil, we know of no studies that have reported ecosystem carbon stocks for this region. However, the several studies reporting aboveground or belowground carbon stocks of tropical and subtropical mangroves and salt marshes in Brazil suggest they are important carbon sinks (Ferreira et al., ; Sanders, Smoak, Naidu, & Patchineelam, ; Sanders, Smoak, Naidu, Sanders, & Patchineelam, ; Sanders, Smoak, Naidu, Araripe et al., ; Suárez‐Abelenda et al., ; Santos et al., ).…”
Section: Introductionmentioning
confidence: 99%